2019
DOI: 10.29271/jcpsp.2019.12.1215
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intra-Osseous Basaloid Squamous Cell Carcinoma of Mandible: Report of Rare Case with Proposed Diagnostic Criteria

Abstract: Basaloid squamous cell carcinoma (BSCC) is a distinctive variant of squamous cell carcinoma (SCC) characterised by nests of basaloid cells. BSCC is an aggressive and rare tumor of head and neck region; and is relatively rare in oral cavity in comparison to SCC. Although, infrequent, but primary intra-osseous SCC (PIOSCC) has been reported in the jaws. There are separate diagnostic criteria for this lesion and a classification for primary intra-osseous carcinoma has been described. No evidence was found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Considering these findings, CMEC or other central malignant tumors should have been considered as a differential diagnosis even if clinical and radiographic findings lacked the features of malignancy. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these findings, CMEC or other central malignant tumors should have been considered as a differential diagnosis even if clinical and radiographic findings lacked the features of malignancy. 19 …”
Section: Discussionmentioning
confidence: 99%
“…However, in our case report, the maxillary radiolucent lesion was accompanied by proliferative and destructive bone lesion in the hard palate and alveolar process. Considering these findings, CMEC or other central malignant tumors should have been considered as a differential diagnosis even if clinical and radiographic findings lacked the features of malignancy 19 …”
Section: Discussionmentioning
confidence: 99%
“…Cortical bone expansion, tooth mobility, pain, and paresthesia were relatively common findings in the selected articles. However, early-stage tumors are commonly included in the differential diagnosis with benign odontogenic lesions, delaying the diagnosis and, consequently, appropriate treatment [5,19,20]. Lukandu et al [19] also pointed out that the late diagnosis of PIOSCC is frequently associated with the absence of imaging tests before exodontia procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Recently, Bajpai et al reported an extremely rare case of intraosseous basaloid SCC in the mandible. 27 In their research, they discussed its immunohistochemical profile also using Ber-Ep4, P63, and EMA. Since basaloid SCC is an aggressive histological subtype of SCC, this study may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bajpai et al reported an extremely rare case of intraosseous basaloid SCC in the mandible 27 . In their research, they discussed its immunohistochemical profile also using Ber‐Ep4, P63, and EMA.…”
Section: Discussionmentioning
confidence: 99%